About the FAIRness of Computable Biomedical Knowledge in Switzerland - Ouaazki, Abdessalam; Cotofrei, Paul (Neuchâtel : Institute of Information Management, 2024)
Computable Biomedical Knowledge (CBK) is a form of knowledge that is machine-understand-able and executable, enabling quick decision-making advice related to human health on a global scale. To maximize the potential of computable knowledge, it should adhere to the FAIR principles (Findable, Accessible, Interoperable, and Reusable), which ensure scientific data's effective discovery, access, and reuse. While there's a growing global trend in adopting FAIR principles, variations in their application exist due to technical and regulatory challenges. Switzerland stands out in global biomedical research with robust healthcare and institutions like the Swiss Institute of Bioinformatics contributing significantly to the field.